ORAL HYGIENE ASSESSMENT THROUGH DIGITAL DENTAL PHOTOGRAPHY IN UNDERGRADUATE MEDICAL STUDENTS OF ARMY MEDICAL COLLEGE RAWALPINDI - Rahima Fouad Khan; Maham Saleem; Laiba Fatima; Fatimah Ashraf (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Oral hygiene plays a crucial role in overall health, yet its assessment in medical students is often overlooked. With advancements in technology, digital dental photography has emerged as a valuable tool for evaluating oral health status in an objective and reproducible manner. Objective: The aim of this study was to evaluate and analyse the degree of oral health awareness together with knowledge and practice skills by using digital dental photography as a screening tool in undergraduate medical students of Army Medical College Rawalpindi.Methods: A total number of participants n=100 where medical students comprised 50 participants and dental students 50 other subjects. The tool which was used to collect the data was digital dental photography, making use of mobile phone cameras, and the collected data was evaluated using various dental indices. Students received a structured questionnaire for self-administration which contained demographics and sections on oral health knowledge about plaque, gum disease and fluoride benefits together with questions about their oral hygiene practices such as brushing, flossing and visits to the dentist. The tool which was used to collect the data was digital dental photography, making use of mobile phone cameras, and the collected data was evaluated using various dental indices. Data was then analyzed using IBM SPSS Statistics 25.0.Results: Results showed that dental students showed superior oral health knowledge 85% together with superior oral hygiene compared to medical students 50%. The scores on plaque recognition along with gum disease awareness and fluoride advantage awareness were statistically higher among dental students when compared to medical students (4.5 vs. 3.2, p = 0.0001; 4.3 vs. 2.8 p = 0.0003). Oral hygiene practices of dental students showed superior results when compared to medical students. Dental students brushed their teeth twice per day at a rate of 90% versus 68% while flossing reached 72% versus 48% and visiting the dentist occurred more often with an average score of 4.5 compared to 2.3 (p = 0.0001). ). A significant number of students were in their fourth year while participants reported ASC as their most prevalent category. High standards indices evaluated the participants' oral health condition. Analysis through DMF Index (median: 1, IQR: 0–2) revealed only minimal presence of dental caries. Oral hygiene was rated positively based on OHI measurements where the median score was 1 and the IQR range lay between 1 and 2. Participants displayed normal dental arrangement through Angle’s Classification (Median 1, IQR 1–1) and their enamel health showed healthy conditions using Dean’s Index (Median 0, IQR 0–1). Participant oral health assessment showed positive results because most students suffered from few dental problems.Conclusions: Digital dental photography shows effectiveness as a screening method to evaluate oral health discrepancies between students at varied ages and educational tiers. Dental students showed better oral health understanding although the study conclusions underline the value of teaching oral healthcare in medical programs. Developing better oral health instruction programs for medical students leads to improved patient care quality. Further study needs to evaluate the effects of dental and medical education convergence on healthcare quality along with patient results.